Decoding classroom dynamics: Unveiling EFL teacher-student interactions at SMAN 1 Bahodopi - Tagor, Fatmi Audisa; Ghozali, Imam (Universitas Sarjanawiyata Tamansiswa, 2023)
The objectives of this study were (1) to describe patterns of teacher-student interaction at SMAN 1 Bahadopi, and (2) to describe the efficacy of the interaction of teacher-students at SMAN 1 Bahadopi. The study was conducted using a descriptive qualitative technique. The source of the data in this research is teacher-student utterances produced during the learning process. The data was recorded, and after recording, the researcher transcribed the data audio recorder into a written transcript. The data has been transcribed. The researcher identified patterns and the efficacy of classroom interaction. The result shows the patterns of teacher-student interaction at SMAN 1 Bahadopi. There were 53 units of interactions developed during the class, consisting of 22 IR, 17 IRF, and 14 Miscellaneous. The efficacy of the interaction between teacher-students at SMAN 1 Bahadopi shows the patterns IR, IRF, and Ii I R F categories, which show an interaction that develops and is successful. The pattern that occurs between teachers and students shows that students can respond to the initiation given by the teacher and understand the learning given. It shows the effectiveness of learning that occurs between teachers and students.